Can therapists be autistic? - Beth Levy (Murmurations)
This article explores a systemic therapist’s dual role as a family therapist and an autistic person, detailing her journey of integrating her autism diagnosis with her professional identity. The article explores autistic communication in reference to the double empathy problem (Milton 2012), the concept that communication difficulties between autistic and non-autistic individuals are due to mutual misunderstandings, and the importance of direct communication in working with autistic clients. It explores the stigma associated with autism and the considerations of disclosing one's autistic status in therapeutic and personal contexts, highlighting the importance of understanding and accommodating autism in therapeutic settings. Therapeutic approaches with autistic people are explored, such as the PPRR model (Burnham 2017). The paper advocates for post-diagnosis support and longer-term work with families, stressing the value autistic therapists bring to the profession by offering unique insights and validation to autistic clients.